(3LRA ef GdbQBf GdcQje (B( (3LRA ef GdLRA GdYGTQ (B)s - (3cdGe Gddg YR hLds
(3ChdgG (B:s
(3bGd JYGdi (B: ( (3hGYdehG CfeG ZfeJe ef TF aEf Gddg NeSg hddQShd hdP GdbQHi hGdjJei hGdeSGcjf hGHf GdSHjd (B) s
(3BNQgG (B:s
(3bGd JYGdi (B( (3hge CZfjGA QVhG HCf jchfhG eY GdNhGda hWHY Gddg Ydi bdhHge age dGjYdehf (B) s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdcJH GdSeGhjIs